Cyberpragmatics Internet-mediated Communication In Context - Yus, Francisco (Pragmatics & Beyond New Series, 2011)
Cyberpragmatics is an analysis of Internet-mediated communication from the perspective of cognitive pragmatics. It addresses a whole range of interactions that can be found on the Net: the web page, chat rooms, instant messaging, social networking sites, 3D virtual worlds, blogs, videoconference, e-mail, Twitter, etc. Of special interest is the role of intentions and the quality of interpretations when these Internet-mediated interactions take place, which is often affected by the textual properties of the medium. The book also analyses the pragmatic implications of transferring offline discourses (e.g. printed paper, advertisements) to the screen-framed space of the Net. And although the main framework is cognitive pragmatics, the book also draws from other theories and models in order to build up a better picture of what really happens when people communicate on the Net.